2017
DOI: 10.1177/0034523717745341
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of occupational stress among urban Indian school teachers

Abstract: Occupational stress among teachers has become a matter of increasing concern. It is not only evidenced from the large body of studies on the subject but also through factors that predispose educators to work related stress. The present study also tends to identify demographic patterns of workplace stress as well as examine the role of correlates like socio-economic status and work experience on stress levels. It further explores specific workplace stressors reported by Indian teachers. The sample consisted of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…, 2015), job insecurity (De Sio et al. , 2018), heavy workload, work experience, and demographic factors (Kaur and Kumar, 2019). Incivility experienced by the teaching faculty in higher educational institutions is a matter of concern as it can make inroads in the teaching-learning environment (Natarajan et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2015), job insecurity (De Sio et al. , 2018), heavy workload, work experience, and demographic factors (Kaur and Kumar, 2019). Incivility experienced by the teaching faculty in higher educational institutions is a matter of concern as it can make inroads in the teaching-learning environment (Natarajan et al.…”
Section: Introductionmentioning
confidence: 99%
“…Various factors have been associated with the onset of work-related stress in teachers. Key stressors among teachers include long work hours (Bannai et al, 2015), time pressure (Aldrup et al, 2017), position in the workplace (Agai-Demjaha et al, 2015), job insecurity (De Sio et al, 2018), heavy workload, work experience, and demographic factors (Kaur and Kumar, 2019). Incivility experienced by the teaching faculty in higher educational institutions is a matter of concern as it can make inroads in the teaching-learning environment (Natarajan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Global studies revealed that high-stakes' accountability, a heavy workload, prolonged work hours, fewer holidays, poor remuneration issues, and intense monitoring were the leading causes of teacher work stress in both private and public management schools (Kaur & Kumar, 2019;Kosalai & Maheswari, 2018;Shkëmbi et al, 2015;Skinner et al, 2021;Viac & Fraser, 2020). Nevertheless, the most critical issue is that stressors for teachers might vary by region.…”
Section: Introductionmentioning
confidence: 99%
“…Rana & Soodan (2019) implied the prominent impact of personal as well as occupational stress on the contentedness and health of the teaching fraternity. Kaur & Kumar (2017) stated that the stress rising from the professions are of a great prominence amongst the school teachers of urban arena. Now-a-days, the teaching and research organizations, particularly the Agricultural Universities and Research organizations are facing new challenges in the context of changing agricultural, social and economic scenario.…”
Section: Introductionmentioning
confidence: 99%